ENGENHARIA REVERSA E BIM PARA EDIFICAÇÕES HISTÓRICAS - Almeida, Tamires; Nascimento, Rodrigo Vinicius C.; Dezen-kempter, Eloisa (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The computational development in Architecture, Engineering, and Construction (AEC), among them the Building Information modeling (BIM), enabled highly improvement in the design, construction and maintenance stages. This paper presents a methodology to create a digital as-is model using reverse engineering. Our work outlines a model-driven approach combining range-based and image-based techniques. Two emblematic buildings of religious architecture in Brazil were surveyed to investigate the integration of multiple reality-based technologies, as well as the processing of the point cloud raw data that allows the creation of a high-resolution Dense Surface Model (DSM), the base of an accurate and detailed parametric Model. The results demonstrated that the interaction between laser scanner and UAV show up as essential to cover the integrity of the building in the reverse engineering process.